3D printing of advanced lithium batteries: a designing strategy of electrode/electrolyte architectures. Issue 45 (9th November 2021) - Pei, Mengfan; Shi, Haiting; Yao, Fengting; Liang, Shuaitong; Xu, Zhiwei; Pei, Xiaoyuan; Wang, Shuo; Hu, Yanli
Abstract : The major applications of 3D-printed technologies in lithium batteries. Abstract : 3D printing, i.e., additive manufacturing, is being progressively applied in lithium batteries to fabricate various electrodes and electrolytes due to the precise design of the structure from the nanoscale to the macroscale. By precisely controlling the geometry and structure, the utilization rate of electrode and electrolyte materials is able to be significantly improved, which is essential for enhancing the energy and power densities of lithium batteries. Herein, the manufacturing strategies and reasoning behind using 3D printing for lithium ion batteries (LIBs) and lithium metal batteries (LMBs) are reviewed. The development trend of electrodes and electrolytes designed by a variety of 3D printing technologies, including direct ink writing (DIW), inkjet printing (IJP), fused deposition modeling (FDM) and stereolithography apparatus (SLA), is summarized. Finally, the future prospects and challenges of 3D-printed lithium batteries are proposed.